Energy System Modeling for Climate-Neutral Transport: Aligning Italian Mobility with EU 2030 and Fit for 55 Goals - Safarzadeh, Hamid; Di Maria, Francesco (Journal of Electronics and Electrical Engineering, 2026)
This study develops an integrated, hourly-resolved, multi-vector energy system model to assess pathways for aligning Italy’s transport sector with the European Union (EU) 2030 and Fit for 55 decarbonisation targets. The model simultaneously represents electricity generation, grid constraints, storage dynamics, hydrogen production, and heterogeneous vehicle charging behaviours. Three scenarios are analysed: Battery Electric Vehicles (BEV)-dominant, Hydrogen-dominant, and Hybrid. Results indicate that the BEV-dominant pathway requires approximately 52 TWh of electricity for vehicle charging, leading to a national peak load of 72 GW and total system costs of €144 billion, while achieving 21.5 Mt CO2 emissions. The Hydrogen-dominant scenario shifts demand toward electrolysis, consuming 45 TWh for hydrogen production (≈1.35 Mt H2 yr−1), reducing emissions to 19.7 Mt CO2 but increasing system costs to€168 billion. The Hybrid scenario balances 38 TWh of direct electricity use with 22 TWh for hydrogen generation, achieving the lowest emissions (17.8 Mt CO2) and moderate costs (€156 billion). Renewable curtailment decreases from 8.3 % (BEV) to 4.5% (Hybrid), highlighting improved flexibility and resource utilization. Overall, the Hybrid configuration demonstrates the most cost-effective and environmentally coherent pathway, integrating both electricity and hydrogen infrastructures. The findings provide quantitative insights for policymakers and system planners seeking to align Italian mobility decarbonisation strategies with EU climate goals while maintaining energy security and affordability.